Heat Shock Protein 70 Surface-Positive Tumor Exosomes Stimulate Migratory and Cytolytic Activity of Natural Killer Cells - Gastpar, Robert (2005)
Detergent-soluble membrane vesicles are actively released by human pancreas (Colo−/Colo+) and colon (CX−/CX+) carcinoma sublines, differing in their capacity to present heat shock protein 70 (Hsp70)/Bag-4 on their plasma membranes. Floating properties, acetylcholine esterase activity, and protein composition characterized them as exosomes. An enrichment of Rab-4 documented their intracellular transport route from early endosomes to the plasma membrane. After solubilization, comparable amounts of cytosolic proteins, including tubulin, Hsp70, Hsc70, and Bag-4, but not ER-residing Grp94 and calnexin, were detectable in tumor-derived exosomes. However, with respect to the exosomal surface, only Colo+/CX+ but not Colo−/CX exosomes were Hsp70 membrane derived positive. Therefore, concomitant with an up-regulated cell surface density of activation markers, migration and Hsp70 reactivity of natural killer (NK) cells was stimulated selectively by Hsp70/Bag-4 surface-positive exosomes, but not by their negative counterparts and tumor cell lysates. Moreover, the exosome-mediated lytic activity of NK cells was blockable by Hsp70-specific antibody. As already shown for TKD stimulation, NK cells preincubated with Hsp70 surface-positive exosomes initiated apoptosis in tumors through granzyme B release. In summary, our data provide an explanation how Hsp70 reactivity in NK cells is induced by tumor-derived exosomes.